Genetic and morphological diversity and population structure of a polyploid complex of Mimosa (Leguminosae). Issue 3 (2nd April 2020) - Morales, Matías; Giannoni, Florencia; Inza, María V.; Soldati, MaríA C.; Bessega, Cecilia F.; Poggio, Lidia; Zelener, Noga; Fortunato, Renée H.
Abstract : Evolutionary processes in plants such as hybridization and polyploidy are relevant to speciation and little studied in subtropical South America. In subtropical South America, the genus Mimosa is highly diverse, comprising 30% of polyploid species. The origin and genetic and morphological structure of polyploids in Mimosa are only very recently investigated, as well as their relevance to speciation, morphological variation, and distribution. Mimosa subser. Dolentes–Brevipedes, a taxonomic complex from that region, exhibits polyploidy, with specific and infraspecific taxa confusedly circumscribed. Studies of its population biology would facilitate the elucidation of evolutionary processes in Mimosa and resolution of taxonomic conflicts. We performed a multidisciplinary study of this complex, analysing seven populations and 87 individuals by means of morphometry, and AFLP fingerprinting throughout its area of distribution. Five populations included several taxa and intermediate individuals. Morphometric analyses revealed three clusters, distinguished mainly by leaf morphology and inflorescence. One population was tetraploid, one was tetraploid/octoploid and the rest octoploid. Genetic differentiation was high ( PhiPT = 0.277) and expected heterozygosity was moderate ( He = 0.190; H = 0.271). Multivariate molecular analyses revealed genetic divergence between highland and lowland grasslands. Structural genetic analyses revealed three clusters: two mixed, distinctly predominant in lowland/highland grasslands; another, exclusively from Mercedes. Molecular analysis of variance showed significant differences between highland/lowland grasslands and cytotypes. Cytotypes and populations differed partially by morphology. Tetraploids were morphologically similar to the sympatric octoploids, showing similar genetic structure and gene flow; furthermore, tetraploids are involved in origin of these higher polyploids. The systematics of this complex requires revision: subseries Dolentes and some Brevipedes species could be considered as one subseries. Admixture of genetic clusters and intermediates can be explained by hybridization and introgression. A marginal population differed from the others by morphology and genetics thus suggesting incipient speciation at the geographic edges of this complex.